Psychosocial adjustment after induced abortion and its explanatory factors among adolescent and adult women - Pereira, Joana (2017)
Objective: To compare the depressive symptoms and quality of life (QoL) among adolescents (<20 years) and adult women who have had an abortion and to explore individual, social, relational and decision-making explanatory factors for (mal)adjustment in each group. Background: International findings are not consistent regarding the presence of negative psychosocial outcomes after abortion or about the explanatory factors for occurrence among adolescents and adult women. Methods: In this cross-sectional study, 177 adolescents (65.1%) and 95 adult women (34.9%) who underwent abortion were recruited. Data on individual, social, relational and decision-making characteristics, depressive symptoms (Edinburgh Postnatal Depression Scale) and QoL (EUROHIS-QOL-8) were collected through self-report questionnaires at 16 healthcare services that provide abortion. Results: Although adolescents are not at greater risk of maladjustment than adult women, abortion may be an emotionally significant event for both age groups. Regarding adolescents, feelings of being pressured into abortion and lower satisfaction with the abortion decision were significantly associated with depressive symptoms and lower QoL. Lower support from the mother was also associated with lower QoL. With regard to adult women, lower satisfaction with the abortion decision was significantly associated with depressive symptoms. None of variables was significantly associated with QoL. Conclusion: Our results suggest that adolescents are not at greater risk of psychosocial maladjustment than are adult women. Factors from different ecological contexts and specific factors depending on age group should be considered in preventive interventions for (mal)adjustment after abortion.